IN VITRO ROOTING OF THE APPLE TREE ROOTSTOCK - M9 RELATED TO SEAL, - SOUZA, Joseane Almeida de; DONINI, Lorena Pastorini; SILVA, Luciane Couto da; CORRÊA, Maria Goreti Senna; SCHUCH, Márcia Wulff (Scientia Agraria, 2007)
The objective for this study was to evaluate two support and two of flask covers and the effect of sucrose on the in vitro rooting of M-9 apple rootstock. The culture medium used was MS, added of indole-3-butyric acid-IBA (5 µM). The treatments consisted of two support (agar or vermiculite); flask cover (cotton-wool or aluminum foil) and with or without addition of sucrose to the culture media. In culture medium with sucrose, it was observed higher rooting percentage with agar than that of vermiculite. The flasks covered with cotton-wool had higher average of root number per plantlet as well as higher rooting percentage in the culture medium with sucrose.